ETHNOECOLOGY IN BUYAN LAKE CONSERVATION - Juliasih, Ni Ketut Ayu; Sudaryati, Ni Luh Gede; Sudiartawan, I Putu; Artha, I Made Dwi Purnama; Panduyasa, I Gede; Suyoga, I Putu Gede (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Ethnoecology is the most recent approach to reveal the complexity of the relationship between belief systems (cosmos), knowledge/cognitive systems (corpus) and praxis (sosio-cultural practices) of local communities which can also be understood as local wisdom. The social phenomena and eco-cultural practices of the people in the Buyan Lake area also show this, so they are appropriately explained on the basis of ethnoecological theory. This qualitative study with descriptive interpretative was carried out for six months (May to October 2023) at the Buyan Lake Area locus. The results of the study show that the people in the Buyan Lake Area really respect the gods who are the rulers of nature who protect the environment of the Buyan Lake Area through the cosmos system, both regarding the mystical belief system revealed in the mythology of the forbidden wood, the gombang-rakrik dragons, the duwe animal, the yellow and the iron soan (springs and channels). Likewise, those who are glorified in the aspect of ruling deities in the Hindu pantheon such as Dewi Danu (lakes gods), Dewi Gangga (river gods), Dewi Gayatri (springs gods), Dewa Vishnu (water gods) and Dewa Sangkara (forest gods). The corpus system concerns their knowledge of the capabilities/availability and utilization of various water resources of Lake Buyan. These two ethnoecological systems form perceptions and underlie practical actions in the form of behavioural adaptations for the conservation of the Buyan Lake Area. The sustainable availability of plant resources around Lake Buyan and its fisheries is also part of its use for periodic rituals (ceremonial means).